Comparison of honeybee behaviour in blooming fruit plantations - Benedek, P.; Nyéki, J.; Szabó, T.; Konrád-Németh, C. (International Journal of Horticultural Science, 2012)
Field observations were made on the fl ower visiting behaviour of honeybee foragers in commercial fruit plantations of apricot, Japanese plums, sour cherry, apple and pear. The number of inspected cultivars was 18. The intensity of fl ower visiting by honey bees was markedly different when data of different fruit species are compared. Most intense bee activity was registered on the Japanese plums, somewhat less on apricots, the intensity diminished signifi cantly with apples and pears. Our data presented on the honeybee visitation of Japanese plums can be regarded as new fi nding because no information has been available so far on the relative attractiveness of this fruit species compared to European fruit tree species. Japanese plums were somewhat more attractive to honeybees than apricot and much more attractive than sour cherry, apple and pear. The behaviour of honeybees as visiting the blooming trees displayed specifi c differences according to the fruit species (apricot, sour cherry, pear), which coincide largely with earlier results. It is notable that the fl ower visiting behaviour of honeybees on Japanese plums has been found to be fairly similar to the same on European plums.